Twin Polymerization at Spherical Hard Templates: An Approach to Size‐Adjustable Carbon Hollow Spheres with Micro‐ or Mesoporous Shells1. Issue 23 (25th April 2013) - Böttger‐Hiller, Falko; Kempe, Patrick; Cox, Gerhard; Panchenko, Alexander; Janssen, Nicole; Petzold, Albrecht; Thurn‐Albrecht, Thomas; Borchardt, Lars; Rose, Marcus; Kaskel, Stefan; Georgi, Colin; Lang, Heinrich; et al.
<x xml:space="preserve">Abstract</x> Kitset hollow spheres: The combination of twin polymerization with hard templates makes hollow carbon spheres (HCSs) with tailored properties easily accessible. The thickness and pore texture of the HCS shells and also the diameter of the spherical cavity can be varied. The application potential of synthesized HCS is substantiated by an excellent cycling stability of lithium–sulfur batteries.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>